Supernumerary tooth in lower incisor region: A case report - Grga Đurica; Dželetović Bojan (Serbian Medical Society - Dental Section, Belgrade, 2010)
Supernumerary teeth are defined as any supplementary tooth in addition to usual configuration of twenty deciduous and thirty-two permanent teeth. They are most commonly found in the anterior maxilla and mandibular bicuspid region. Although supernumerary teeth have been reported in the incisor region of the mandible, they are very rare. It has been confirmed that approximately 25% of permanent supernumerary teeth appear in the mouth, the rest remains unerupted. The aim of this study was to present a case of single, erupted, supernumerary tooth in the right incisal region of the mandible. A patient showed up at the dental office complaining about aesthetic problem caused by a supernumerary tooth in mandibular incisal region. On intraoral examination, a supernumerary tooth, conical in shape and labially positioned, between the tooth 42 and 43, was observed. On previously taken panoramic radiogram, six months ago, the supernumerary tooth was undetected. Because the supernumerary tooth was masked by the denser overlying cortical bone, it was difficult to interpret the radiogram correctly. It should be noted that panoramic radiography does not guarantee accurate diagnosis of supernumerary teeth, therefore additional diagnostic methods are required.